Patterns of infestation, dispersion, and gene flow in Rhyzopertha dominica based on population genetics and ecological modeling - Cordeiro, Erick M. G. (Kansas State University, 2016)
Movement is a fundamental feature of animals that impacts processes across multiple scales in space and time. Due to the heterogeneous and fragmented nature of habitats that make up landscapes, movement is not expected to be random in all instances, and an increase in fitness is an expected consequence for those that can optimize movement to find valuable and scarce recourses. I studied the movement of Rhyzopertha dominica (Coleoptera: Bostrichidae), one of the most important pests of stored grain worldwide, within and between resource patches. At a fine spatial scale, I identified factors that contribute to overall and upward movement in the grain mass. Three-week-old insects tented to stay closer to the surface than one or two-week-old insects. Females tended to be more active and to explore more than males. I also found that males tended to stay closer to the surface than females and that might be related to the ability to attract females from outside the patch since there was no significant difference regarding female’s attraction within the grain patch. Interaction with feeding sites or other individuals of the same sex creates positive feedback and a more clumped spatial pattern of feeding and foraging behavior. On the other hand, interaction with individuals of different sex creates negative feedback and a more random or overdispersed pattern. At a broad spatial scale, I studied the long-term consequence of R. dominica movement on the development of population structure within the U.S. To evaluate population structure, I used reduced representation of the genome followed by direct sequencing of beetles collected from different locations across the U.S where wheat or rice is produced and stored. Ecoregions were more important in explaining structure of R. dominica populations than crop type. I also found significant isolation by distance; however, model selection primarily elected grain production and movement variables to explain population differentiation and diversity. Understanding animal movement is essential to establishing relationships between distribution and surrounding landscape, and this knowledge can improve conservation and management strategies.
Keywords: Lesser grain borer; Model selection; AIC; Stored product; Innate orientation; Movement within the patch; Genotyping by sequencing; Modeling; Population genetics